PENGARUH QUALITY OF WORK LIFE DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI YANG DIMEDIASI MOTIVASI KERJA (Studi Pada Pegawai Bank BPD Bali Cabang Negara) - Ni Luh Putu Fitriana Hapsari; Arief Purwanto; Muchlis Mas’ud (Jurnal Cakrawala Ilmiah, 2024)
The aim of this research is to empirically analyze the influence of quality of work life and work discipline on employee performance which is mediated by work motivation (Study of Bank BPD Bali State Branch Employees). In this research, researchers used a quantitative approach. The population in this study were all employees of Bank BPD Bali State Branch, totaling 76 employees. The researcher chose the sample using a saturated sampling technique because the population was relatively small. So the sample used in this research was 76 respondents. The data analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS version 4 software. The research results show that quality of work life is unable to improve employee performance. Quality of work life is unable to increase work motivation. Work discipline is able to improve employee performance. Work discipline is able to increase work motivation. Work motivation is able to improve employee performance. Work motivation does not play a role in mediating quality of work life in improving employee performance. Work motivation plays a role in mediating work discipline in improving the performance of Bank BPD Bali State branch employees.